Origin : a novel - Brown, Dan (New York : Anchor Books, 2017)
In Origin, Harvard symbologist Robert Langdon is invited to Bilbao's Guggenheim Museum for a groundbreaking announcement by his former student, futurist Edmond Kirsch. When the presentation becomes a violent spectacle, Langdon escapes with Ambra Vidal, the museum$1 (Bs director. Their journey takes them to Barcelona, deciphering puzzles and uncovering secret vaults$1 (Bwhile evading forces determined to suppress Kirsch$1 (Bs controversial revelation. Combining art, religion, and cutting-edge science, this high-stakes thriller tackles the question: Where do we come from, and where are we going?s
Keywords: Mysteries -- Fiction; Suspense fiction; Conspiracy fiction; Symbology -- Fiction; Barcelona -- Fiction